Diagnostic Accuracy of Intraoperative Touch Imprint Cytology for the Diagnosis of Axillary Sentinel Lymph Node Metastasis of Breast Cancer: Comparison With Intraoperative Frozen Section Evaluation - Hashmi, Atif A (Cureus, 2021)
Introduction The intraoperative frozen section is a recommended method to detect breast cancer metastasis to axillary sentinel lymph nodes (SLNs); however, frozen section is not widely available and requires an experienced staff. Alternatively, touch imprint cytology (TIC) is a simple and cost-effective technique to detect metastasis. Therefore, in this study, we assessed the diagnostic accuracy of TIC for detecting SLN metastasis and compared it with intraoperative frozen section evaluation. Methodology A retrospective study was conducted in the Department of Histopathology, Liaquat National Hospital and Medical College, for a duration of two years. A total of 114 patients undergoing surgery for primary breast cancer were included in the study. All patients had clinically and radiologically negative axillary lymph nodes. SLN sampling was done using radioactive dye and sent for intraoperative consultation. The SLNs were sliced at 4-mm intervals and two TIC slides and three step-levels for frozen section were prepared, and the results were compared with final (paraffin) section histology. Results The sensitivity, specificity, and diagnostic accuracy of TIC was 83.7%, 98.5%, and 92.1%, respectively. Alternatively, the sensitivity, specificity, and diagnostic accuracy of frozen section was 93.9%, 100%, and 97.4%, respectively. The sensitivity of TIC and frozen section for detecting micrometastasis was 14.3% and 57.1%, respectively, with a diagnostic accuracy of 90.3% and 95.8%, respectively. Alternatively, with respect to macrometastasis, the sensitivity and specificity of TIC were 95.2% and 98.5%, respectively, while the sensitivity and specificity of frozen section were 100%. Conclusion TIC is a quick and effective technique for detecting breast cancer metastasis in axillary SLNs. Although frozen section had an overall higher sensitivity than TIC, the sensitivity of TIC for detecting macrometastasis was comparable to the frozen section. Therefore, we conclude that TIC is a good alternative to the frozen section in facilities where the frozen section is not available.